2011
DOI: 10.1039/c1mt00041a
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of oxaliplatin adducts with DNA nucleotides

Abstract: This paper describes a set of fast and selective high performance liquid chromatography (HPLC) methods coupled to electro-spray ionisation linear ion trap mass spectrometry (ESI-MS), sector-field inductively coupled plasma mass spectrometry (SF-ICP-MS) and UV detection for in vitro studies of the bifunctional adducts of oxaliplatin with mono-nucleotides, di-nucleotides and cellular DNA. The stationary phases and the optimised conditions used for each separation are discussed. Interaction of oxaliplatin with A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
(50 reference statements)
0
32
0
Order By: Relevance
“…These adducts were also characterized with UV absorption data and SF‐ICP‐MS elemental 195 Pt and 31 P signals. Further, interaction of oxaliplatin with AG and GG di‐nucleotides resulted in the formation of three adducts: DACHPt‐GG and two isomers of the DAC (Zayed et al, ) DACHPt‐AG adduct was confirmed with ESI‐MS and complementary data obtained from UV and SF‐ICP‐MS. An LC‐ICP‐MS method to quantify oxaliplatin GG intra‐strand adducts (DACHPt‐GG) was developed and used to monitoring the in vitro formation and repair of these adducts in human colorectal cancer cells.…”
Section: Dna Adduct Analysismentioning
confidence: 83%
“…These adducts were also characterized with UV absorption data and SF‐ICP‐MS elemental 195 Pt and 31 P signals. Further, interaction of oxaliplatin with AG and GG di‐nucleotides resulted in the formation of three adducts: DACHPt‐GG and two isomers of the DAC (Zayed et al, ) DACHPt‐AG adduct was confirmed with ESI‐MS and complementary data obtained from UV and SF‐ICP‐MS. An LC‐ICP‐MS method to quantify oxaliplatin GG intra‐strand adducts (DACHPt‐GG) was developed and used to monitoring the in vitro formation and repair of these adducts in human colorectal cancer cells.…”
Section: Dna Adduct Analysismentioning
confidence: 83%
“…Under the specific conditions of this experiment, cisplatin produces 1–5 adducts per 10 6 DNA nucleotides, a level of modification typically observed in cisplatin-treated cells and in DNA isolated from clinical samples. 14, 15 Compound 1 produced irreversible damage with DNA at a significantly higher frequency of up to 25 adducts per 10 6 nucleotides. Likewise, compound 1 showed considerably more efficient DNA binding in experiments in which NCI-H460 cells were incubated with compound 1 and cisplatin for 12 h, but at their respective 90% inhibitory concentrations (IC 90 values were 94 nM for compound 1 vs. 11 μM for cisplatin, determined in 72-h incubations).…”
Section: Resultsmentioning
confidence: 99%
“…For quantification at levels below the ESI detection limit, LC/ICP‐MS monitoring of platinum content has been established; the reliable quantification of DNA adducts is under scrutiny right now.…”
Section: Resultsmentioning
confidence: 99%